2013
DOI: 10.1111/coa.12135
|View full text |Cite
|
Sign up to set email alerts
|

Healing outcomes of large (>50%) traumatic membrane perforations with inverted edges following no intervention, edge approximation and fibroblast growth factor application; a sequential allocation, three‐armed trial

Abstract: ObjectiveThe goal of this study was to evaluate the effects of perforation edge approximation and direct application of basic fibroblast growth factor (bFGF) each alone on the healing of large traumatic tympanic membrane perforations with inverted edges in humans.Study DesignProspective, sequential allocation, three-armed, controlled clinical study.SettingUniversity-affiliated teaching hospital.ParticipantsFifty-eight patients with large traumatic tympanic membrane perforations (i.e. affecting >50% of the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…The 83% success rate demonstrated in this study is comparable with published conventional myringoplasty series [3], but is lower than that demonstrated by other authors utilizing bFGF [8,9,16]. One Table 2 Operating theatre cost analysis between conventional underlay myringoplasty procedure and trial FGF procedure (all figures in Australian dollars).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The 83% success rate demonstrated in this study is comparable with published conventional myringoplasty series [3], but is lower than that demonstrated by other authors utilizing bFGF [8,9,16]. One Table 2 Operating theatre cost analysis between conventional underlay myringoplasty procedure and trial FGF procedure (all figures in Australian dollars).…”
Section: Discussionsupporting
confidence: 65%
“…In Hakuba's study [13] cholesteatoma was first identified up to 17 months post-treatment suggesting that long-term follow-up is indicated for patients undergoing this technique. Lou and Wang [8] reported the development of myringitis in 52% of cases in whom gelatin sponge was utilized, however CT imaging confirmed the absence of any middle ear or mastoid inflammation in these cases and the myringitis did not have any effect on hearing outcome or patient symptoms. None of our patients treated with bFGF and gelfoam developed the myringitis described by Lou and Wang.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Using off label growth factors, without demonstrating safety and nonototoxicity in nonhuman models, in patient populations with wounds that likely would have healed without treatment and without long-term follow-up should be considered ''risky.'' [20][21][22][23][24][25] …”
mentioning
confidence: 99%